APLIKASI MARKETPLACE BERBASIS SISTEM PENDUKUNG KEPUTUSAN UNTUK PEMESANAN DAN PEMASANGAN IKLAN PADA BILLBOARD DI KOTA DENPASAR - Dedi Pradnya Iswara, I Made; Arsa Suyadnya, I Made; Arya Mertasana, Putu (Jurnal SPEKTRUM; Vol 9 No 1 (2022): Jurnal SPEKTRUM, 2022)
Billboards are a great form of outdoor advertising. Billboards containing text or images of information promoting a product are usually taken by the advertising agency. Advertising companies promote curated billboards using individual websites, requiring clients to switch between sites to get billboards that meet the criteria. The purpose of marketplace creation is to avoid customers having to switch sites for billboards that meet the criteria. The marketplace is built using Laravel 7 framework with additional features of a business intelligence system to help customers get billboards based on their criteria. The decision support system uses a weighted accumulation method that uses multiplication to relate the scoring criteria, where the score of each criterion will be increased by the weight of the related criteria. The use of a decision support system with a weighted product approach as a support function on a market site is the use of a decision support system as a recommendation for the application market. The result of this research is that a web-based marketplace with a decision support system has been successfully built using the Laravel 7 framework and MySQL DBMS. Based on the black box tests performed on the app, it performs according to its function and based on theoretical comparison testing related to the use of the weight product method, the results of the recommendations on the billboard application are in accordance with manual calculations.